2008
DOI: 10.4314/ajtcam.v5i1.31261
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, Analgesic And Anti-Inflammatory Effects Of The Ethylacetate Extract Of The Leaves Of <i>Pseudocedrella kotschyii</i>

Abstract: Phytochemical screening was carried out on the ethylacetate portion of the ethanolic extract of the leaves of Pseudocedrella kotschyii and then evaluated for its analgesic (acetic acid-induced writhing) and anti-inflammatory (raw egg albumin-induced oedema) activities in mice and rats respectively. Phytochemical screening of the ethylacetate partition portion of ethanolic extract revealed the presence of flavonoids, glycosides and tannins as major chemical constituents. Alkaloids saponins, cardiac glycosides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…The animals were randomized into five groups (n = 6/group) and fasted for 6 h. Groups 1-3 received 100, 200, and 400 mg/kg per os, respectively, of the extract solubilized in 5% Tween 80; no anesthesia was utilized for the application. Group 4 rats received piroxicam (20 mg/ kg, per os); piroxicam is an effective non-steroidal anti-inflammatory drug that has been routinely used as a standard for comparison in these types of studies (Musa et al, 2008;Ayanwuyi et al, 2010). Rats in group 5 served as the negative control and were given only the vehicle (5% Tween 80 solution).…”
Section: Acute Toxicity (Ld 50 ) Testmentioning
confidence: 99%
“…The animals were randomized into five groups (n = 6/group) and fasted for 6 h. Groups 1-3 received 100, 200, and 400 mg/kg per os, respectively, of the extract solubilized in 5% Tween 80; no anesthesia was utilized for the application. Group 4 rats received piroxicam (20 mg/ kg, per os); piroxicam is an effective non-steroidal anti-inflammatory drug that has been routinely used as a standard for comparison in these types of studies (Musa et al, 2008;Ayanwuyi et al, 2010). Rats in group 5 served as the negative control and were given only the vehicle (5% Tween 80 solution).…”
Section: Acute Toxicity (Ld 50 ) Testmentioning
confidence: 99%
“…It should also be mentioned that, EHE produced significant (P<0.05) analgesic activity compared to the standard, diclofenac-Na at a dose of 9 mg/kg. Moreover analgesic effects have already been established in flavonoids, tannins and alkaloids (Musa et al, 2008;Zulfiker et al, 2010) therefore it is possible that the anti-nociceptive effects observed in the extracts may be attributed due to its phytochemical constituents.…”
Section: Resultsmentioning
confidence: 99%
“…Although, a low level of chronic inflammatory response is beneficial, but at the high or severe condition it may cause harm to the host (Islam et al 2016b). The plant-derived constituents, such as alkaloids and glycosides are known to produce a number of biological activities, including antipyretic, analgesic, anti-inflammatory, and so on (Musa et al 2008;Nur et al 2015;Sultana et al 2015). For an example, in a study, Sidaye et al (2011) reported that the antipyretic action of the plant crude extract can inhibit the prostaglandin synthesis in experimental animals.…”
Section: Discussionmentioning
confidence: 99%